Butyrate Inhibits Colorectal Cancer Cell Proliferation through Autophagy Degradation of β-Catenin Regardless of APC and β-Catenin Mutational Status - Beatrice Garavaglia; Letizia Vallino; Alessandra Ferraresi; Andrea Esposito; Amreen Salwa; Chiara Vidoni; Sergio Gentilli; Ciro Isidoro (Biomedicines, 2022)
Colorectal cancer (CRC) pathogenesis is mainly driven by alterations in WNT signaling, which results in altered transcriptional activity of β-Catenin. Mutations in APC (Adenomatous Polyposis Coli) are reflected in β-Catenin hyperactivation and loss of proliferation control. Certain intestinal bacteria metabolites have shown the ability to limit CRC cell proliferation and CRC pathogenesis. Here, we investigated the molecular mechanism underlying the anti-proliferative activity of butyrate, a microbiota-derived short chain fatty acid, in two CRC cell lines, namely HCT116 and SW620, which bear a mutation in β-Catenin and APC, respectively. In particular, we focused on autophagy, a lysosome-dependent degradation pathway, which was shown to control intestinal tissue homeostasis. Butyrate reduced CRC cell proliferation, as witnessed by the downregulation of proliferation markers. TCGA bioinformatic transcriptomic analysis of CTNNB1 (β-Catenin) gene correlation in CRC patients showed that β-Catenin negatively correlates with the autophagy gene ATG4D. In CRC cells, regardless of the mutational state of APC or β-Catenin genes, butyrate caused the autophagy-mediated degradation of β-Catenin; thus, preventing its transcriptional activity. Autophagy gene silencing restored β-Catenin levels, allowing it to translocate into the nucleus to promote the expression of downstream genes associated with cancer cell proliferation. CRC-affected patients show driver mutations in the WNT pathway; thus, targeting its crucial effector may be a promising therapeutic strategy in CRC treatment; for instance, by using ad hoc probiotics that stimulate autophagy.